COGNITIVE AND LEXICAL-SEMANTIC PROPERTIES OF ADJECTIVES PHARASEMES CHARACTER IN ENGLISH AND UZBEK - Karimkulov Abbduvakkos Chinberdiyevich (Academia Science Repository, 2023)
This article discusses the scientific-theoretical aspects of the semantic and linguocultural characteristics of phraseology in English and Uzbek languages.